EVALUASI PARTISIPASI MASYARAKAT DALAM E-GOVERNMENT PELAYANAN PUBLIK DI KABUPATEN BOYOLALI - Mohammad Toha Putra; Warsito .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
Bureaucracy reform demands bring information technology to take part in government, especially in public service innovation. Bureaucracy reform is done through E-Government policy, in this case public service innovation is done by online system. Department of Investment and Integrated Services One Door Kabupaten Boyolali has implemented online licensing which is also part of ¬E-Government. However, in its application there are some barriers that is in the citizens participation. Facts found that citizens participation to use online permissions are very low. The research method used in this research is mix method approach with data collection technique through the questionnaire and interview, also document study. Respondents in this study are people who take care of licensing and informants of this study are people who work in Section of Information and Documentation Division of Investment and Integrated Service Department One Door Boyolali District.The result of the research shows that the factors that influence the low of public participation in using the online permission are the knowledge of the society about the low of the socialization in online licensing, the ability of the community to use the supporting facilities / infrastructures which are not yet optimal, the quality of the internet network is inadequate in some areas, Low online services, and awareness of people who want change but not in line with the attitude of people who want to use online licensing.Recommendations that can be given to the implementation of E-Government as an innovation of public services in encouraging licensing services in Boyolali District is the Department of Investment and Integrated Services One Door Boyolali District as the party that implements online permissions in order to give socialization back evenly with methods that are easily accepted by citizens. For the citizens try to support the bureaucratic reform effort in Boyolali District through E-Government especially through online permission and willing to abandon the old way to achieve their needs effectively and efficiently. For the private sector concerned to participate in supporting government policy, especially E-Government by improving equity of supporting facilities such as internet network development to the areas that still unreachable.